Сподівання на штучний інтелект для України - Бєгун, В. В.; Бєгун, С. В. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Обґрунтовано доцільність та необхідність впровадження штучного інтелекту у сферу безпеки України з відповидним вдосконаленням освітніх програм ВНЗ.

The feasibility and necessity of introducing artificial intelligence into the security sphere of Ukraine with the corresponding improvement of educational programs of higher education institutions are substantiated.
Hopes for artificial intelligence for Ukraine
Keywords: штучний інтелект; безпека України; освітні програми; безпека життєдіяльності; цивільний захист; artificial intelligence; security of Ukraine; educational programs; civil protection